A new method to prepare low melting point polyamide‐6 and study crystallization behavior of polyamide‐6/calcium chloride complex by rheological method. Issue 8 (4th October 2014) - Liu, Dianxin; Zheng, Qiang; Lu, Shengjun; Li, Cheng; Lu, Pan; Yu, Jie
ABSTRACT A new method to prepare low melting point polyamide‐6 (LPA6) by complex reaction of calcium chloride (CaCl2) and polyamide‐6 (PA6) in a co‐rotating twin screw extruder was reported. We employed a new rheological method to study the crystallization behavior of PA6/CaCl2 complex and the mechanism of confined crystallization of PA6. Compared with differential scanning calorimetry (DSC), this method was more capable of detecting crystalline information. What's more, it was also an effective method for studying mechanism of confined crystallization. From the results of X‐ray diffraction, DSC, infrared spectroscopy, rheology, and mechanical properties, the complex reaction of CaCl2 with the carbonyl oxygen atom in the amide group disrupted the intermolecular hydrogen bonding and confined the mobility of PA6 molecules. This could significantly reduce the crystallinity and melting temperature of PA6, and improve tensile strength and notched Izod impact strength. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41513.